A Genome-wide Screen for Neurospora crassa Transcription Factors Regulating Glycogen Metabolism - Goncalves, Rodrigo Duarte [UNESP]; Cupertino, Fernanda Barbosa [UNESP]; Freitas, Fernanda Zanolli [UNESP]; Luchessi, Augusto Ducati; Bertolini, Maria Celia [UNESP] (Amer Soc Biochemistry Molecular Biology Inc, 2011)
Transcription factors play a key role in transcription regulation as they recognize and directly bind to defined sites in promoter regions of target genes, and thus modulate differential expression. The overall process is extremely dynamic, as they have to move through the nucleus and transiently bind to chromatin in order to regulate gene transcription. To identify transcription factors that affect glycogen accumulation in Neurospora crassa, we performed a systematic screen of a deletion strains set generated by the Neurospora Knockout Project and available at the Fungal Genetics Stock Center. In a wild-type strain of N. crassa, glycogen content reaches a maximal level at the end of the exponential growth phase, but upon heat stress the glycogen content rapidly drops. The gene encoding glycogen synthase (gsn) is transcriptionally down-regulated when the mycelium is exposed to the same stress condition. We identified 17 deleted strains having glycogen accumulation profiles different from that of the wild-type strain under both normal growth and heat stress conditions. Most of the transcription factors identified were annotated as hypothetical protein, however some of them, such as the PacC, XlnR, and NIT2 proteins, were biochemically well-characterized either in N. crassa or in other fungi. The identification of some of the transcription factors was coincident with the presence of DNA-binding motifs specific for the transcription factors in the gsn 5'-flanking region, and some of these DNA-binding motifs were demonstrated to be functional by Electrophoretic Mobility Shift Assay (EMSA) experiments. Strains knocked-out in these transcription factors presented impairment in the regulation of gsn expression, suggesting that the transcription factors regulate glycogen accumulation by directly regulating gsn gene expression. Five selected mutant strains showed defects in cell cycle progression, and two transcription factors were light-regulated. The results indicate that there are connections linking different cellular processes, such as metabolism control, biological clock, and cell cycle progression. Molecular & Cellular Proteomics 10: 10.1074/mcp.M111.007963, 1-13, 2011.